2015
DOI: 10.1590/s0080-623420150000500003
|View full text |Cite
|
Sign up to set email alerts
|

Primary Health Care from the perception of women living in a rural area

Abstract: Objective: Understanding the perception of women living in a rural area about the actions and services of Primary Health Care (PHC) in a municipality of southern Brazil, which is the only one regarded as predominantly rural. Method: A descriptive study of qualitative approach, carried out with women who lived in the countryside and required health services in the 15 days prior to collection. Results: The results registered low fidelity to PHC attributes, focusing its functional axis on sickness, transforming t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
0
15
0
5
Order By: Relevance
“…Therefore, it is common for professionals to find difficulties in performing care, with a view to reducing service shifts by location, generating care gaps, and compromising the comprehensiveness of health care. Some studies show that there is little possibility of a change in care model in rural areas, where access to basic health services is low, with a high population that seeks specialized and hospital care (16)(17)(18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is common for professionals to find difficulties in performing care, with a view to reducing service shifts by location, generating care gaps, and compromising the comprehensiveness of health care. Some studies show that there is little possibility of a change in care model in rural areas, where access to basic health services is low, with a high population that seeks specialized and hospital care (16)(17)(18) .…”
Section: Discussionmentioning
confidence: 99%
“…Considering the accessibility of the service, a study evaluated the satisfaction of FHS users in the rural area of two small municipalities of Rio Grande do Norte, which revealed as a negative point the daily non-permanence of professionals in the units of their localities (17) . Another research carried out in the rural area of the city of Prudentópolis, Paraná State, showed that health professionals worked in a fragmented way, serving more than one locality in a short space of time, which influenced the quality of care (16) .…”
Section: Discussionmentioning
confidence: 99%
“…In rural areas of Brazil, health services have lower supply and quality, as well as greater difficulty in accessing the Primary Health Units, resulting in an inequality between supply and demand in urban and rural areas 5 . In the latter, the demand for care is almost always motivated by acute diseases 6 . Thus, the population receives services based on demand and not on organized supply according to its supposed or perceived needs [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…In the latter, the demand for care is almost always motivated by acute diseases 6 . Thus, the population receives services based on demand and not on organized supply according to its supposed or perceived needs [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in rural settings, the situation of families is more complex, since they face other difficulties that are not noticed in urban areas, such as insufficient public transportation, lack of health services and, in many regions, lack of infrastructure, like electricity and means of communication (11)(12) . These deficiencies create greater obstacles for the work of rural FHS teams.…”
Section: Introductionmentioning
confidence: 99%